Murine model evaluation of biochemical and tissue-damage induced by Bothrops asper (Nauyaca) snake venom - Gallardo-Casas, Dr. Carlos Gallardo-Casas Ángel; Valadez-Omaña, María Teresa; Correa Solís, Emmanuel; Castillo-Hernández, María del Carmen; Ortiz-Butron, Rocio (Medicina e Investigación Universidad Autónoma del Estado de México; Vol. 13 Núm. 1 (2025): Revista de Medicina e Investigación Universidad Autónoma del Estado de MéxicoDO - 10.36677/medicinainvestigacion.v13i1.24277, 2025)
Introduction : Venomous snakes Bites are a serious public health issue, and in Mexico, Bothrops asper is responsible for the majority of viper bites.  Objective : To evaluate, in a mouse model, the effect of Bothrops asper venom snake on liver enzymes LDH, AST, and ALT, as well as to assess its effect on renal and hepatic histology.  Methods : The LD50 was determined using a dose-response curve after intramuscular administration of increasing doses of the venom to mice (0.5, 1, 2.5, 5, and 10 mg of protein/kg). Subsequently, the mice were administered the LD25 value of the venom (or saline solution for control), and 24 hours after the injection, LDH, AST, and ALT enzymes were measured in the blood, and the liver and kidneys were collected from each animal.  Results : Results: Animals treated with poison (LD25 of 1 mg of protein/kg) had greater activity of AST, ALT and LDH enzymes, structural damage in the cortex and renal medulla, as well as in the liver after 24 hours of administration in the experimental group Conclusion : B. asper venom causes an increase in LDH and transaminase enzymes, as well as renal and hepatic histopathological alterations.